You've got a friend in me: How social networks and mobile phones facilitate healthcare access among marginalised groups in rural Thailand and Lao PDR. (January 2021) - Haenssgen, Marco J.; Charoenboon, Nutcha; Zanello, Giacomo
Highlights: New digital inequalities among marginalised groups could be amplified by the recent widespread of health-related phone use. Using treatment-seeking data from households in Thailand and Laos, we address equality in technological development interventions. We document a broad spectrum of "informal" health-related mobile phone uses alongside widespread health-related social support. We show that health-related phone use and social support facilitate public healthcare access among marginalised groups. Long-term crowding out of social support and competition between formal and informal mHealth risk to intensify health access inequalities. Abstract: The seeming "ubiquity" of mobile phones has spawned a wave of interventions that use mobiles as platforms for health service delivery (mHealth). Operating in more than 100 countries, mHealth interventions commonly aspire to make healthcare more inclusive and efficient. Yet, mobile phone diffusion also stimulates locally emerging forms of health-related phone use that could create new digital inequalities among marginalised groups or compete with mHealth and other technology-based development interventions. We aim to inform this subject by asking, " How do mobile phone use and social support networks influence rural treatment-seeking behaviours among marginalised groups? " We hypothesise that (1) resource constraints drive marginalised groups towards informal healthcare access, and that (2) mobile phone use and social support networks facilitate access to formal healthcare with a bias towards private doctors. Analysing representative survey data from 2141 Thai and Lao villagers with descriptive statistics and multi-level regression models, we demonstrate that: (a) health-related phone use is concentrated among less marginalised groups, while social support networks are distributed more equitably; (b) marginalised villagers are more likely to utilise informal healthcare providers; and (c) mobile phones and social support networks are linked to increased yet delayed formal healthcare access that is directed towards public healthcare. We conclude that mobile phone diffusion has a mildly positive association with rural healthcare access, operating in a similar fashion but without (yet) appearing to crowd out social support. However encouraging, this is problematic news for mHealth and technology-based development interventions. The potential behavioural consequences of "informal mHealth" reinforce the notion that mobile phones are a non-neutral platform for mHealth and development interventions. The long-term implications require more research, but the literature suggests that increasing phone-aided healthcare facilitation could undermine local social support networks and leave already marginalised rural dwellers in yet more precarious circumstances.